2021
DOI: 10.1186/s13059-021-02469-x
|View full text |Cite
|
Sign up to set email alerts
|

AMULET: a novel read count-based method for effective multiplet detection from single nucleus ATAC-seq data

Abstract: Detecting multiplets in single nucleus (sn)ATAC-seq data is challenging due to data sparsity and limited dynamic range. AMULET (ATAC-seq MULtiplet Estimation Tool) enumerates regions with greater than two uniquely aligned reads across the genome to effectively detect multiplets. We evaluate the method by generating snATAC-seq data in the human blood and pancreatic islet samples. AMULET has high precision, estimated via donor-based multiplexing, and high recall, estimated via simulated multiplets, compared to a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 26 publications
(52 reference statements)
2
50
0
Order By: Relevance
“…We next investigated whether scDblFinder could be applied to other types of single-cell data prone to doublets, such as single-cell Assay for Transposase-Accessible Chromatin sequencing (ATACseq). We compared scDblFinder to two methods specifically designed to scATACseq: the ArchR package ( Granja et al 2021 ), which implements a doublet detection method that is also based on the comparison to artificial doublets, and the AMULET method ( Thibodeau et al 2021 ). AMULET is based on the assumption that, in a diploid cell, any given genomic region should be captured at most twice, and therefore interprets a larger number of loci with more than two reads as indicative of the droplet being a doublet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next investigated whether scDblFinder could be applied to other types of single-cell data prone to doublets, such as single-cell Assay for Transposase-Accessible Chromatin sequencing (ATACseq). We compared scDblFinder to two methods specifically designed to scATACseq: the ArchR package ( Granja et al 2021 ), which implements a doublet detection method that is also based on the comparison to artificial doublets, and the AMULET method ( Thibodeau et al 2021 ). AMULET is based on the assumption that, in a diploid cell, any given genomic region should be captured at most twice, and therefore interprets a larger number of loci with more than two reads as indicative of the droplet being a doublet.…”
Section: Resultsmentioning
confidence: 99%
“…The methods were compared across three datasets where a genotype-based annotation was available as ground truth: two obtained from Granja et al (2021 ; GSM4957261 and GSM4957262), which by design do not have homotypic doublets, and the dataset published along AMULET (GSM5457171; Thibodeau et al 2021 ). The latter contains homotypic doublets, but its doublet annotation is highly incomplete: due to the low number of individuals multiplexed, we expected to have approximately 35% of the doublets within-individual, and hence mislabeled as singlets.…”
Section: Resultsmentioning
confidence: 99%
“…We removed potential doublet cells by the number of regions with per-base coverage greater than 3 (Ref. 16 ). We also removed fragments with interval length smaller than 10 that are likely to be misalignment.…”
Section: Methodsmentioning
confidence: 99%
“…Pseudo bulk peak positions for each cell type were identified using MACS2 ( Zhang et al, 2008 ). In addition, we used Amulet ( Thibodeau et al, 2021 )to detect multiplets, which identified 532 nuclei (∼7.5%) as multiplets. These nuclei were removed to visualize the read coverage and TSR enrichment plots.…”
Section: Methodsmentioning
confidence: 99%